Staatsangehörigkeit und Rassismus Rechtsdiskurse und Verwaltungspraxis in den Kolonien Eritrea und Deutsch-Ostafrika (1882-1919) - Camilleri, Nicola (Global Perspectives on Legal History, 2021)
When Italy and Germany joined the 'scramble for Africa' and established colonies on the continent in the late 19th century, they, like other imperial powers before them, had to deal with the question of how to define the legal status of the inhabitants of these territories. This book takes Eritrea and German East Africa as case studies to comparatively analyze norms and practices of citizenship. It focuses on racism and other elements that influenced colonial governmentality.